33.0k views
4 votes
If
z=-1-√(3)i and
z^(6)=a+bi, then
a = _ and
b = _

User Bisw
by
4.9k points

1 Answer

2 votes

Rewriting
z in polar form makes this trivial.


z=|z|e^{i\mathrm{arg}(z)}

We have


|z|=√((-1)^2+(-\sqrt3)^2)=2


\mathrm{arg}(z)=\tan^(-1)(-1,-\sqrt3)=-\frac{2\pi}3

(not to be confused with the standard inverse tangent function
\tan^(-1)x. Here
\tan^(-1)(x,y) is the inverse tangent function that takes into account position in the coordinate plane; look up "atan2" for more information)

So we have


z=-1-\sqrt3\,i=2e^(-2\pi/3\,i)

Then


z^6=2^6\left(e^(-2\pi/3\,i)\right)^6=64e^(-4\pi\,i)=64

so that
a=64 and
b=0.

User Chaoix
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.